Blow-up rate of sign-changing solutions to nonlinear parabolic systems in domains. (September 2022) - Zhanpeisov, Erbol
Abstract: We present a blow-up rate estimate for a solution to the parabolic Gross–Pitaevskii and related systems on a convex domain with Sobolev subcritical nonlinearity. We also obtain a blow-up rate estimate on a nonconvex domain under additional assumptions.